Development of a Professional Activity Model on Readiness Preparation to Enhance Student Teachers’ Desirable Characteristics for an Industrial Education Program in Agricultural Education - Junlek, Piyanard; Keawurai, Wareerat; Nopparak, Sombat; Shinatrakool, Ravewan (Kasetsart Journal of Social Sciences, 2014)
The main purpose of this research was to develop a professional activity model on readiness preparation to enhance student teachers’ desirable characteristics for an industrial education program in agricultural education. It was divided into 4 steps: (1) studying fundamental data; (2) constructing and validating a professional activity model; (3) verifying the professional activity model with 39 student teachers from the Industrial Education Program in Agricultural Education at the King Mongkut’s Institute of Technology Ladkrabang; and (4) evaluating the student teachers satisfaction with the model. The collected data were analyzed through qualitative and quantitative data analysis techniques. The results revealed that two aspects of desirable characteristics are: (1) communication and using information technology and (2) learning design by five stages of guidelines in the process of activity arrangement; survey, observation, decision-making, action, and, reflection—the so-called SODAR model. The professional activity model consisted of 7 factors: background, fundamental concepts in development, principles, objectives, structure and content, activity arrangement, and evaluation using the SODAR model which was applied to the factors of activity arrangement and it was verified at a high level of possibilities and appropriateness. The student teachers’ desirable characteristics were higher than before: (1) communication, using information technology, and learning design after participation in the activities were higher at a significant level of .01; (2) skills in communication, using information technology, and learning design after participation in the activities were higher than those in the set criteria by up to 75 percent at a significant level of .01; (3) attitudes toward communication, using information technology, and learning design after participating in the activities were higher at the significant level of .01; and (4) the professional activity model was evaluated as providing a high level of satisfaction.